Database of geomagnetically induced currents in the main transmission line “Northern Transit” - Selivanov V. N.; Aksenovich T. V.; Bilin V. A.; Kolobov V. V.; Saharov Y. A. (Solar-Terrestrial Physics, 2023)
Database containing the results of measurements of geomagnetically induced currents (GIC) for the period of 2011 to 2022 in transformer neutrals at three 330 kV substations of the main power transmission lines “Northern Transit” passing through the territory of the Republic of Karelia, Murmansk and Leningrad regions has been created and is publicly available. The GIC value depends on the geoelectric field magnitude in the Earth surface, on the relative position of the substations to which the power transmission lines are connected, and on the resistance of electrical network elements. Important factors are the electrical network branching, which determines paths of induced current spreading, and the network topology at the time of monitoring data acquisition. We describe the structure and principles of functioning of the Russian unique regional monitoring system of geomagnetically induced currents in the electrical network. We demonstrate the features of the data contained in the GIC database, which must be taken into account when processing and analyzing the data. Examples of using the GIC database for energy and geophysical studies are given. The work performed on the organization of continuous monitoring of GIC at substations of the main power transmission line in the Arctic zone has no analogues in the Russian Federation and provides extensive original material that allows us to study geomagnetic disturbances and their impact on electrical networks. The database is available at [http://gic.en51.ru]